2006
DOI: 10.1093/geronb/61.2.s62
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use as Health Self-Management: Rural Older Adults With Diabetes

Abstract: . The majority of respondents used some form of CAM for general purpose, whereas far fewer used CAM for diabetes care. The most widely used CAM categories were food home remedies, other home remedies, and vitamins. The following health self-management predictors were related to the use of different categories of CAM therapies: personal characteristics (ethnicity), health status (number of health conditions), personal resources (education), and financial resources (economic status). Discussion. CAM is a widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
108
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 29 publications
8
108
0
1
Order By: Relevance
“…Those who are strict in their own self-discipline are believed to have a tendency to spend more on both therapies. Previous reports have suggested that those patients seeking CAM believe that it offers them more personal autonomy and control over their health care decisions [22,23]. In addition, the growth in CAM may be due to the ascendancy of patient self-empowerment [24], which may explain our findings regarding SMBG as an independent factor of CAM.…”
Section: Discussionmentioning
confidence: 60%
“…Those who are strict in their own self-discipline are believed to have a tendency to spend more on both therapies. Previous reports have suggested that those patients seeking CAM believe that it offers them more personal autonomy and control over their health care decisions [22,23]. In addition, the growth in CAM may be due to the ascendancy of patient self-empowerment [24], which may explain our findings regarding SMBG as an independent factor of CAM.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the movement for self-care occurred shortly after, and CAM may provide people with a better sense of control and responsibility over the management of their disease. 28,29 We hypothesize that more baby boomers will turn to CAM because of a growing interest in self-management programs that emphasize the patient's role in managing chronic diseases. Previous studies reported older adults integrating CAM with conventional practices to treat daily symptoms related to their chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported older adults integrating CAM with conventional practices to treat daily symptoms related to their chronic disease. 29 Herbs, dietary supplements, and mind-body medicine are commonly reported modalities for self-management. 18 Current clinical trials for mind-body approaches such tai chi and yoga show emerging evidence demonstrating an improvement in quality of life for those with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, surveys of rural older adults with diabetes using lists that include a wide variety of home remedies have found higher CAM use than other surveys that exclude home remedies. 7 Lumping CAM remedies or therapies into broad categories (e.g., ''Herbs'' or ''Manipulative Therapies'') may result in lower use estimates than splitting the modalities into multiple discrete items (e.g., ''Ginseng'' and ''Echinacea,'' or ''Chiropractic'' and ''Shiatsu''). Open-ended formats or a single closed question, in contrast, may result in underestimating CAM use because of respondents' failure to remember CAM use or because they do not consider their practices to be CAM.…”
Section: Background: Need For a Common Instrumentmentioning
confidence: 99%
“…Other studies try to identify ''current use.'' This is sometimes specified as in the past 12 months 7,13 or as during the course of an illness. 14 All of these issues regarding sampling and measurement suggest that the use of a common, standard questionnaire will facilitate comparisons between studies.…”
Section: Background: Need For a Common Instrumentmentioning
confidence: 99%